Trusting in Psychotherapy. - Allen, Jon G. (American Psychiatric Association Publishing, 2021)
"Cultivating trusting psychotherapy bonds is complex, challenging, and a critically important topic. In Trusting in Psychotherapy, the author posits that trusting cannot be understood apart from trustworthiness and that therapists should give equal attention to the task of becoming trustworthy to their patients. Blending developmental science and ethical thought, the author elucidates such topics as what it means to trust in the practice of psychotherapy; the many facets of trusting and trustworthiness; attachment relationships; the central role of hope in trust; and the ethical-moral basis of trusting and trustworthiness"--